A new species of Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from Guizhou, China - Yan, Jie; Lin, Yubo; Guo, Weibo; Li, Peng; Zhou, Kaiya (Zootaxa, 2016)
A new species of the genus Hemiphyllodactylus is described from Huishui County, Guizhou Province, Southwest China. Hemiphyllodactylus huishuiensis sp. nov. is distinguished from all other congeners by having the unique combination of the following characters: a maximum SVL of 51.2 mm; 8 or 10 chin scales; enlarged postmental scales; 3 circumnasal scales; 2 or 3 scales between the supranasals; 9–11 supralabials; 9–11 infralabials; 13–15 dorsal scales; 7–9 ventral scales; a lamellar hand formula of 3-4-4-4 or 4-4/5-5-4; a lamellar foot formula of 4-4/5-5-4/5; 3 subdigital lamellae on the first finger and first toe; a continuous precloacal and femoral pore series of less than 20; one cloacal spur in both males and females; no enlarged subcaudal scales; dark dorsal transverse blotches; dark postorbital stripe; a brown postsacral mark bearing anteriorly projecting arms; and unpigmented caecum and gonads. The new species also occurs in Ziyun County, Guizhou Province, China.